Market Dynamics in Digital Business in Indonesia: a Study of Competition, Innovation, and Consumer Trends - Icin Quraysin; Atik Cahyawati; Ayat Muhammad Aatulla; Egi Ginanjar; Okafia Azizah; Yayu Humairoh (SEAN Institute, 2026)
This study aims to analyze the influence of competition, innovation, and consumer trends on market dynamics in digital businesses in Indonesia. The rapid development of the digital economy requires businesses to be able to adapt to changes in the business environment, technology, and consumer behavior. The study used a quantitative approach with a survey method of 100 respondents consisting of business owners, managers, and employees in the digital business sector in Indonesia. The sampling technique used purposive sampling with the criteria of respondents having at least one year of experience in digital businesses. Data collection was conducted through an online questionnaire using a Likert scale. Data analysis used multiple linear regression with the help of validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and coefficients of determination. The results of the study indicate that partially, competition has a positive and significant effect on market dynamics, innovation has a positive and significant effect and is the most dominant variable, and consumer trends also have a positive and significant effect on market dynamics. Simultaneously, competition, innovation, and consumer trends have a significant effect on market dynamics with a contribution of 61.2%. These findings indicate that the success of a digital business is largely determined by the company's ability to face competition, create sustainable innovation, and understand changing consumer needs. This study is expected to be a reference for the development of digital business strategies in Indonesia.